(untitled) (Acta Scientiarum. Animal Sciences, 2018)
The objective of this study was to select sorghum genotypes for silage production. The study was carried out at Embrapa Maize & Sorghum’s experimental field. Planting was performed in randomized blocks, with three replicates and the Scott-Knott test at a 5% probability level. The material was ensilaged in laboratory silos opened after 56 days for analysis concerning fermentation and bromatological composition. Only crude protein showed no significant difference (p > 0.05), with an overall mean of 8.88%. The other variables presented significant differences (p < 0.05): pH (3.34 to 3.94); Aw (0.93 to 0.98); N-NH 3/TN (1.61 to 6.56%); green matter yield (12.05 to 34.14 t ha-1); dry matter yield (6.19 to 11.42 t ha-1); dry matter (26.89 to 49.95%); ashes (4.08 to 6.88%); neutral detergent fiber corrected for ash and protein (47.67 to 65.79%); acid detergent fiber (16.62 to 35.89%); hemicellulose:cellulose (1.07 to 2.71%); lignin (2.03 to 6.52%), digestible dry matter yield (3.70 to 7.41 t ha-1) and dry matter digestibility (56.36 to 72.67%). Based on digestible dry matter yield, the genotypes: male 201191 and hybrids 2012F47484, 2012F47515 and 2012F47525 stood out in relation to the others for showing good yielding, adequate nutritional value, with low dry matter and NDF levels coupled with high digestibility values and good fermentation patterns of the silages.